El Salvador : Request for Stand-By Arrangement; Staff Report; Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for El Salvador. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report for El Salvador's request for a Stand-By Arrangement is examined. Fiscal consolidation led to a reduction in the public debt-to-GDP ratio, and the country has experienced the highest growth rates in a decade. Real GDP growth is projected to slow to 3.2 percent in 2008, reflecting lower growth in remittances, a tightening of external financing conditions, and a decline in investment. Exports, however, have remained buoyant despite weaker external demand. The banking system remains liquid and well capitalized, although nonperforming loans have increased and profitability is declining.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet